Wheat fiber from a residue to a reinforcing material - Albahttiti, Mohammed T. (Kansas State University, 2012)
Throughout history natural fiber was used as one of the main building materials all over the world. Because the use of such materials has decreased in the last century, not much research has been conducted to investigate their performance as a reinforcing material in cement and concrete. In order to investigate one of the most common natural fibers, wheat fibers, as a reinforcing material, 156 mortar specimens and 99 concrete specimens were tested. The specimens were tested in either uniaxial compression or flexure. The uniaxial compression test included 2 in (50.8 mm) mortar cubes and 4x8 in (101.6 x 203.2 mm) concrete cylinders. As for the flexure test, they were either 40x40x160 mm cementitious matrix prisms or 6x6x21 in (152.4x152.4x533.4 mm) concrete prisms. Several wheat fibers percentages were studied and compared with polypropylene fiber as a benchmarking alternative. The average increase in the uniaxial compression strength for cementitious matrix cubes reinforced with 0.5% long wheat fiber exceeded that of their counterparts reinforced with polypropylene fiber by 15%. Whereas for concrete cylinders reinforced with 0.75% long wheat fiber, their strength exceeded that of their counterparts reinforced with polypropylene fiber by 5% and that of the control by 7%. The flexural strength of cementitious matrix prisms reinforced with 0.75% long wheat fiber exceeded that of their counterparts reinforced with polypropylene fiber by 27%. Meanwhile, concrete prisms reinforced with both long wheat fiber and polypropylene fiber showed deterioration in strength of up to 17%. Finally, ABAQUS models were developed for concrete cylinders and prisms to simulate the effect of inclusion of the wheat fibers.
Keywords: Natural fibers; Concrete; Cementitious matrix; Finite element modeling; Mortar; Fiber Reinforcement; Wheat Fibers; Uniaxial Compression; Flexural; Abaqus Simulations; Architectural engineering (0462); Civil Engineering (0543); Environmental Engineering (0775); Materials Science (0794)